WEBGIS technology for management and sharing spatial data of protected area, a case study in Xuan Lien nature reserve, Thanh Hoa - Quynh, Ha Quy; Phuong, Dang Huy; Phuong, Nguyen Tien (Vietnam Journal of Science and Technology, 2016)
Resource management in National parks (NP), Nature reserve (NR) aim to hold the status of biological resources of the area [4]. Up to now, Vietnam has established 31 NP and about 100 NR. Most of NR, NP was completed build biological database [4]. The traditional information sharing method has showed the limitations, causing many difficulties for the users, particularly when exploring the map information. WebGIS technology developed quickly with the functions included: internet access, query spatial data in the Internet, which has promoted the possibility aid, consult spatial data, link between tables and map [1, 5, 7]. Biodiversity Database of Xuan Lien NR was built based on tables and maps. The table database is designed as relational data, including the information and records. With animals is Class - Order - Family – Species and plants is Plant - Phylum - Family - Species. The code of the species included 4 parts. One part of character and 3 parts of numbers. The database are the records of 1142 plant species, 55 mammal species, 190 birds, 38 reptiles and 35 amphibians species. The map database include base map, zonation map, infrastructure maps, vegetation and distribution map of species in protected areas. Display Biodiversity data of NR by MapServer, showing base map, zonation map, infrastructure maps, vegetation and habitat map. Using the combined technologies of Remote Sensing, GIS and WebGIS to manage, display, sharing biodiversity data of NR promotion optimization capabilities in data analyses and combined tables with map. This technology may apply for management biodiversity database of all protected areas in Vietnam.